2011
DOI: 10.1177/0003319711412763
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Parameters and Angiographic Progression of Coronary Atherosclerosis

Abstract: Hematologic parameters have prognostic importance in cardiovascular disease. However, the relation between atherosclerosis progression and hematologic parameters is not well defined. A total of 394 patients requiring repeat coronary angiography were included in the study. According to angiography, patients were divided into 2 groups, progressive (n = 196) and nonprogressive (n = 198) diseases. Hematologic parameters including mean platelet volume (MPV) and neutrophil/lymphocyte (N/L) ratio were measured. Gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 20 publications
(35 reference statements)
7
114
0
2
Order By: Relevance
“…In the present study, it was found as a main finding that RVD was significantly associated with neutrophil and lymphocyte count, and the NLR. The NLR has been evaluated in coronary artery disease and acute coronary syndromes [25][26][27]. Kaya et al [28] evaluated the role of the NLR in patients with STEMI undergoing PCI and found that NLR is an independent predictor of both inhospital and long-term adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was found as a main finding that RVD was significantly associated with neutrophil and lymphocyte count, and the NLR. The NLR has been evaluated in coronary artery disease and acute coronary syndromes [25][26][27]. Kaya et al [28] evaluated the role of the NLR in patients with STEMI undergoing PCI and found that NLR is an independent predictor of both inhospital and long-term adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] Kalay et al reported that NLR is a marker for progression of atherosclerosis in coronary artery disease. 28 It has also been shown that NLR is a marker for possible cardiac events and mortality in patients with stable coronary artery disease. Another study demonstrated a relationship between NLR and severe coronary artery disease and claimed that it could be used to predict moderate-severe coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Gated Miyokard Perfüzyon SPECT Görüntüleme Çalışmaya dahil edilen hastalar için uygulanacak MPS için radyofarmasötik olarak Tc-99m sestamibi kullanıldı. Hastalara stres görüntülemede 296-370 MBq (8)(9)(10) (6) Jung ve arkadaşlarının yaptığı bir çalışmada, çok kesitli bilgisayarlı tomografi kullanılarak belirlenebilen koroner kalsiyum skoru ile MPV arasındaki ilişki araştırılmıştır. 2116 kişi ile yapılan çalışmada MPV değeri kontrol grubuna göre koroner arter kalsifikasyonu grubunda anlamlı olarak yüksek bulunmuştur.…”
Section: Gereç Ve Yöntemler Hasta Seçimiunclassified